A study on the rights of access to justice under our constitution / Sasha Diana Sabtu, Aina Azahra Arifin and Azizudin Adam Mudin - Sabtu, Sasha Diana; Arifin, Aina Azahra; Adam Mudin, Azizudin (2006)
This thesis is with regards to the fundamental rights in Malaysia under our constitution, where it specifically deals with the rights of access to justice under Part II of the Federal Constitution. The main concern of the thesis is regarding the issue on the difficulties faced by the public in acquiring the rights to access to courts or tribunals which provides remedy for the aggrieved. The current position in Malaysia is that although fundamental rights are guaranteed under the constitution, which supposedly be the supreme law of the land, the rights conferred by the Constitution could easily be abrogated by way of the Act of Parliament and economic factors. Comparison of the written constitution is made between India and Malaysia in order to measure to what extent the fundamental rights conferred to the people is being guaranteed under the constitution. The research also includes study on relevant cases in relation to the issue. As 'all are equal before the law and are entitled to equal protection of the law', legal aid can be seen as fundamental human rights. Hence, the issue of legal aid is also discussed in the research. Few methods of research has been adopted in the process of completing this thesis which includes case study, library research; studies on textbooks, magazines, articles and statutes, and made observations, surveys and interviews.